Tuesday

July 22, 2014

July 22, 2014

Posted by **asdf** on Thursday, November 29, 2012 at 5:04pm.

I can use the anti-derivatives to get

y = 2x^3 + Cx + D

but I don't know how to get C even though I know D = 1.

- calculus -
**Steve**, Thursday, November 29, 2012 at 5:08pmyou know that

y' = 6x + C

and that y'(0) = 0, so

0 = C

y = 2x^3 + 1

- calculus -
**asdf**, Thursday, November 29, 2012 at 5:56pmSo y'(0) = 0 because there is a horizontal tangent at x = 0?

**Related Questions**

calculus - Consider the curve defined by 2y^3+6X^2(y)- 12x^2 +6y=1 . a. Show ...

Help Calc.! - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+y^2+1...

please help; calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy)/(x^2+...

calculus - A curve passes through the point (1,-11) and it's gradient at any ...

calculus - Suppose y is defined implicitly as a function of x by x^2+Axy^2+By^3=...

Need help fast on calc - original curve: 2y^3+6(x^2)y-12x^2+6y=1 dy/dx=(4x-2xy...

Calculus - Damon - Find the line which passes through the point (0, 1/4) and is ...

calculus - Find the equation of a straight line that passes through a point (1,5...

calculus - the tangent line to the curve y=x^2 at the point (a,a^2) passes ...

Calculus - Sketch a graph of the parabola y=x^2+3. On the same graph, plot the ...